Genetic counselling, BRCA1/2 status and clinico-pathologic characteristics of patients with ovarian cancer before 50 years of age - Cvelbar, Mirjam (Radiology and oncology (Ljubljana), 2017)
In Slovenia like in other countries, till recently, personal history of epithelial ovarian cancer (EOC) has not been included among indications for genetic counselling. Recent studies reported up to 17% rate of germinal BRCA1/2 mutation (gBRCA1/2m) within the age group under 50 years at diagnosis. The original aim of this study was to invite to the genetic counselling still living patients with EOC under 45 years, to offer gBRCA1/2m testing and to perform analysis of gBRCA1/2m rate and of clinico-pathologic characteristics. Later, we added also the data of previously genetically tested patients with EOC aged 45 to 49 years. Patients and methods. All clinical data have to be interpreted in the light of many changes happened in the field of EOC just in the last few years: new hystology stage classification (FIGO), new hystology types and differentiation grades classification, new therapeutic possibilities (PARP inhibitors available, also in Slovenia) and new guidelines for genetic counselling of EOC patients (National Comprehensive Cancer Network, NCCN), together with next-generation sequencing possibilities. Results. Compliance rate at the invitation was 43.1%. In the group of 27 invited or previously tested patients with EOC diagnosed before the age of 45 years, five gBRCA1/2 mutations were found. The gBRCA1/2m detection rate within the group was 18.5%. There were 4 gBRCA1 and 1 gBRCA2 mutations detected. In the extended group of 42 tested patients with EOC diagnosed before the age of 50 years, 14 gBRCA1/2 mutations were found. The gBRCA1/2m detection rate within this extended, partially selected group was 33.3%. There were 11 gBRCA1 and 3 gBRCA2 mutations detected. Conclusions. The rate of gBRCA1/2 mutation in tested unselected EOC patients under the age of 50 years was higher than 10%, namely 18.5%. Considering also a direct therapeuthic benefit of PARP inhibitors for BRCA positive patients, there is a double reason to offer genetic testing to all EOC patients younger than 50 years. Regarding clinical data, it is important to perform their re-interpretation in everyday clinical practice, because this may influence therapeutic possibilities to be offered.
Keywords: BRCA 1/2; genetic counseling; genetsko svetovanje; ovarian cancer; rak jajčnikov